(untitled) (Confluenţe Bibliologice, 2025)
Libraries were not always staffed by professionals. In the old days, the work of librarians was taken on by writers, philosophers, and scientists. On the eve of Librarian Day, we remember people who were symbols of culture, creative power, living legends, and librarians!